Russia's frozen frontier : a history of Siberia and the Russian Far East, 1581-1991 - Wood, Alan, 1943- (Bloomsbury Academic, 2011)
Alan Wood's ambitious work is the first to address the whole span - both chronologically and thematically - of the development of Siberia, and its role in both the Russian and the global context. With a scope that reaches from to Muscovy's conquest of Siberia in the 16th and 17th centuries to modern times, it explores the effects of colonial exploitation, the Revolutions of 1917 and developments during the Soviet period. Russia's Frozen Frontier is also the first book to detail the history of Siberia from the view of Siberians themselves - both Russian and native - rather than seen through the.